Detection of Pseudomonas aeruginosa pus wound isolate using a polymerase chain reaction targeting 16S rRNA and gyrB genes: A case from Indonesia - Jamaluddin, Indra P.; Musa, Susan H.; Ethica, Stalis N.; Ansori, Arif NM.; Yosephi, Valensa; Atmaja, Peter Y.; Murtadlo, Ahmad AA.; Sahadewa, Sukma; Durry, Fara D.; Rebezov, Maksim; Derkho, Marina; Naw, Sin W.; Zainul, Rahadian; Rachmawati, Kadek (Narra Sains Indonesia, 2024)
Infectious wounds on the skin surface are easily colonized by bacteria from pyogenic group that manifest as inflammation, such as Pseudomonas aeruginosa. P. aeruginosa is a Gram-negative bacterium and an opportunistic pathogen known for causing invasive state in critically ill and immunocompromised patients. The aim of this study was to detect the 16S rRNA and gyrB genes in P. aeruginosa using polymerase chain reaction (PCR) method. The sample in this study was pus isolate from a 5-year-old boy with leg wounds. The bacteria were isolated on brain heart infusion broth (BHIB) media and identified with molecular identification. Sequencing and BLAST analysis were carried out to determine the similarity of gene identity by comparing sample sequence with other isolate sequences on the Gene Bank. The results of molecular identification showed amplification DNA band of around 934 base pairs (bp) for 16S rRNA and 225 bp for gyrB gene. The BLAST program demonstrated that the sample had 99.89% similarity with P. aeruginosa strain XC4 (accession code ON795960.1) for the 16S rRNA gene. Meanwhile, the gyrB gene exhibited 99.10% similarity with the P. aeruginosa strain PSA-1.2 (accession code KP172300.1).